THE YIELD AND ISOTOPIC COMPOSITION OF RADIOLYTIC H2, A POTENTIAL ENERGY SOURCE FOR THE DEEP SUBSURFACE BIOSPHERE - Lin L.-H.; Onstott T.C.; Slater G.F.; Sherwood Lollar B.; Lacrampe-Couloume G. (My University, 2005)
The production rate and isotopic composition of H2 derived from radiolytic reactions in H2O were measured to assess the importance of radiolytic H2 in subsurface environments and to determine whether its isotopic signature can be used as a diagnostic tool. Saline and pure, aerobic and anaerobic water samples with pH values of 4, 7, and 10 were irradiated in sealed vials at room temperature with an artificial γ source, and the H2 abundance in the headspace and its isotopic composition were measured. The H2 concentrations were observed to increase linearly with dosage at a rate of 0.40 ± 0.04 molecules (100 eV)-1 within the dosage range of 900 to 3500 Gray (Gy; Gy = 1 J Kg-1) with no indication of a maximum limit on H2 concentration. At ~2000 Gy, the H2 concentration varied only by 16% across the experimental range of pH, salinity, and O2. Based upon this measured yield and H2 yields for α and β particles, a radiolytic H2 production rate of 10-9 to 10-4 nM s-1 was estimated for the range of radioactive element concentrations and porosities typical of crustal rocks. The δD of H2 (δD = ((D/H)sample/ (D/H)standard - 1) × 1000) was independent of the dosage, pH (except for pH 4), salinity, and O2 and yielded an αDH2O-H2 of 2.05 ± 0.07 (αDH2O-H2 = (D/H)H2O to (D/H)H2), slightly less than predicted radiolytic models. Although this radiolytic fractionation value is significantly heavier than that of equilibrium isotopic exchange between H2 and H2O, the isotopic exchange rate between H2 and H2O will erase the heavy δD of radiolytic H2 if the age of the groundwater is greater than ~103 to 104 yr. The millimolar concentrations of H2 observed in the groundwater of several Precambrian Shields are consistent with radiolysis of water that has resided in the subsurface for a few million years. These concentrations are well above those required to support H2-utilizing microorganisms and to inhibit H2-producing, fermentative microorganisms. Copyright © 2005 Elsevier Ltd.
Keywords: Precambrian